FMF Is Associated With a Wide Spectrum of MHC Class I- and Allied SpA Disorders but Not With Classical MHC Class II-Associated Autoimmune Disease: Insights From a Large Cohort Study - Watad, Abdulla; Bragazzi, Nicola Luigi; Adawi, Mohammad; Shoenfeld, Yehuda; Comaneshter, Doron; Cohen, Arnon D.; McGonagle, Dennis; Amital, Howard (Frontiers in Immunology, 2019)
Objectives: To test the hypothesis that familial Meditteranean fever (FMF) associated autoinflammation may exaggerate the tendency towards adaptive immunopathology or spondyloarthritis (SpA)-associated disorders including MHC class-I associated disorders but not classical MHC class II-associated disorders that exhibit transplacental autoimmunity including myasthenia gravis and pemphigus. Methods: 7,747 FMF patients and 10,080 age- and sex-matched controls in the Clalit-Health-Services medical database were identified and compared in terms of prevalence of SpA-associated disorders and also evaluated 4 classical and strong MHC class-II associated disorders, namely pemphigus vulgaris, myasthenia gravis, sarcoidosis and pernicious anaemia, to ascertain whether such associations with SpA-spectrum disease were specific or merely reflected the non-specific consequences of innate immune system activation on driving divergent types of immunity. Results: FMF showed a strong association with MHC class I related diseases: OR 28.58 ([95%CI 6.93-117.87], p<0.0001) for Behçet’s disease, OR of 10.33 ([95%CI 4.09-26.09], p<0.0001) for AS, and OR 1.67 ([95%CI 1.19-2.33], p=0.0029) for psoriasis. For weakly MHC class I linked diseases, an OR of 3.76 ([95%CI 2.48-5.69], p<0.0001) for Crohn’s disease and OR of 2.64 ([95%CI 1.52-4.56], p=0.0005) for ulcerative colitis were found. No association was found between FMF and the four MHC class II-associated autoimmune disorders. Conclusion: FMF patients are associated with increased risk of SpA-related disease diagnosis including MHC-I-opathies but not MHC-II associated autoimmune diseases suggesting that tissue-specific dysregulation of innate immunity share between FMF and SpA spectrum disorders may drive adaptive immune MHC class I-associated conditions.